2022
DOI: 10.3390/ijerph19031500
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence and Its Association with Physical and Psycho-Cognitive Factors: A Cross-Sectional Study in Older People Living in Nursing Homes

Abstract: Urinary incontinence (UI) is a common geriatric syndrome affecting bladder health and is especially prevalent in nursing homes (NHs). The aim of the study was to determine the prevalence of UI and its associated factors in five Spanish NHs. UI (measured with Minimum Data Set 3.0.), sociodemographic, and health-related variables were collected. Chi-square (or Fisher’s) or Student’s t-test (or Mann Whitney U) for bivariate analysis were used, with Prevalence Ratio (PR) as an association measure. The prevalence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
0
6
0
1
Order By: Relevance
“…Furthermore, pausing group activities, especially physical exercise and outdoor activities, exacerbated the development of sarcopenia, frailty, and functional decline 24 . Activity patterns can have an impact on pelvic floor health, even in NH residents, with emerging evidence on the relationship between sedentary behavior and UI 25 . In this line, a study conducted in Spain showed a significant functional, cognitive, and nutritional decline in NH residents after the first wave of the pandemic, which was attributed to the lockdown itself, because no differences were found between COVID‐19 and non‐COVID‐19 individuals 2…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pausing group activities, especially physical exercise and outdoor activities, exacerbated the development of sarcopenia, frailty, and functional decline 24 . Activity patterns can have an impact on pelvic floor health, even in NH residents, with emerging evidence on the relationship between sedentary behavior and UI 25 . In this line, a study conducted in Spain showed a significant functional, cognitive, and nutritional decline in NH residents after the first wave of the pandemic, which was attributed to the lockdown itself, because no differences were found between COVID‐19 and non‐COVID‐19 individuals 2…”
Section: Discussionmentioning
confidence: 99%
“…Decline in physical performance has been associated with urinary incontinence in older women [ 40 42 ]. Existing literature supports a bidirectional relationship between physical function and urge urinary incontinence: worsening urinary incontinence is associated with worsening physical function including increased fall risk, and conversely, deterioration of physical function is associated with the development of urinary incontinence [ 7 , 41 46 ].…”
Section: Association Between Urinary Incontinence and Falls In Older ...mentioning
confidence: 99%
“…An association between urgency UI and SB bouts, defined as the accumulation of uninterrupted and prolonged SB periods, have been found in community-dwelling older women [ 20 ]. Emerging research suggests that the duration of SB bouts may have a higher impact on continence than the total amount of time spent in SB throughout the day [ 20 , 21 ]. However, there are still few studies on this topic, especially in frail older adults and NH residents.…”
Section: Introductionmentioning
confidence: 99%